To investigate the success and failure factors of ERP implementation within Malaysian small and medium enterprises - Noudoostbeni, A.; Yasin, N.M.; Jenatabadi, H.S. (2009)
In recent years ERP, as a comprehensive new system, has been used by many Malaysian companies. It has been successful in some and in some others it has failed. This article assesses 15 success factors and 8 failure factors in SME companies and tries to recognize the effective ones. The results show that the two most important failure factors in implementing ERP in Malaysian SMEs are 'poor planning or poor management' and 'inappropriate training methods' and the most important success factors are I Implementing team's teamwork and composition' and 'Effective training of users'. It could be conducted that team work is a key success factor in Malaysian SMEs and also training is of vital importance. As a result, by a sound investment and effective trainings we may guarantee the success of ERP in SMEs in Malaysia, failure to do so will lead to a defeat for ERP in Malaysian setting.